Suppression of the brain-pituitary-testicular axis function following acute arsenic and manganese co-exposure and withdrawal in rats (2017)
Despite the fact that most environmental exposures to metals do not occur in isolation, the combined effects of metal mixtures on brain–pituitary–gonadal axis are poorly known. The present study investigated the impacts of co-exposure to arsenic (As) and manganese (Mn) on sperm characteristics, reproductive hormones and selected oxidative stress indices in the brain, testes and epididymis of rats following exposure for 15 consecutive days to 60 mg/L of AsO₃Na and 30 mg/L of MnCl₂ in drinking water. The results showed that while brain weight remained unaffected, the fluid intake and the weights of testes and epididymis significantly (p < 0.05) decreased in all the treatment groups. A significant decrease in the body weight gain when compared with control was noted only in the co-exposed rats. Moreover, the significant decreases in the antioxidant status in brain, testes and epididymis as well as in the circulatory concentrations of follicle-stimulating hormone, luteinizing hormone and testosterone were similar following separate or combined exposure of rats to As and Mn. The marked oxidative damage in the investigated tissues was accompanied by a significant decrease in the sperm quantity and quality in all the treated rats when compared with the control. Interestingly, most of the parameters determined immediately after the exposure period persisted in rats from the withdrawal experiment. Collectively, co-exposure to As and Mn suppressed the brain–pituitary–testicular axis function and the post-testicular events such as sperm function possibly via a mechanism involving persistent oxidative stress and endocrine disruption in the exposed rats.